Multispectral ecological control of biomass of phytoplankton in aqueous media in situ using a quadrocopter - Kvaterniuk, Serhii; Petruk, Vasyl (Lviv Politechnic Publishing House, 2018)
The aim of the work is to improve the method and means of multi-spectral ecological control of phytoplankton biomass in water environments in situ using a quadrocopter with a multi-spectral camera. The instrumental and methodological errors of indirect measurements of phytoplankton biomass in the near-surface layer of the aquatic environment using the developed means of environmental control have been analyzed.
Keywords: ecological monitoring; multispectral measurements; water; phytoplankton; bioindication